Development Analysis of Post Graduate School Program of Occupational Health Nursing (OHN), Workforce and The Challenges in Poltekkes Kemenkes Jayapura (a Case Study) - Isak Jurun Hans Tukayo; Syaifoel Hardy; Moh. Saljan; I Ketut Swastika (Journal of Ners and Midwifery, 2021)
Background: According to the Central Statistics Agency (BPS, 2020), Papua is one of the poorest provinces in Indonesia with a poverty rate of 26.8%. This condition is exacerbated by the lack of educational facilities including occupational health nursing (OHN) at the postgraduate level. Even though there are several large industries in Papua that are engaged in oil exploration to wood processing. As a result, there is an imbalance between the need for OHN nursing experts and the production of nurses due to the absence of OHN postgraduate educational facilities in Papua.Destination: This article is a case study which aims to analyze the development of OHN postgraduate education programs, human resources and challenges from an Occupational Safety and Health (OHS) perspective.Method: The study used is in the form of a literature review using SWOT Analysis which emphasizes on policy issues on nursing education and its specialties, especially OHN. Data is collected from various sources, including the Ministry of Health, the Ministry of Manpower, BPPSDM, PPNI, journals from within and outside the country. Document review was conducted from January 2016 to December 2020.Result: From the results of the SWOT analysis, the research shows that the Poltekkes of the Ministry of Health of Jayapura has a very supportive potential to develop postgraduate nursing education programs in the OHN department. In addition to adequate human resources, sufficient land for practice and the availability of industrial jobs for graduates.